On the impact of the soft handoff threshold and the maximum size of the active group on resource allocation and outage probability in the UMTS system. - Avidor, D. (IEEE Transactions on wireless communications)
We study the effect of two control parameters of the universal mobile telecommunication system handoff algorithm on resource allocation and the outage probability of the forward link. We thereby provide information on the effect of the parameters on the probability distributions of the number of base stations (BSs) supporting a mobile station (MS), the number of MSs supported by a single BS (per carrier), and the maximal cell size, subject to a given probability of downlink outage on the cell boundary. Denoting the set of BSs supporting an MS in soft handoff as the active group, the first parameter nA is the maximum allowed size of the active group. The second, denoted τ, is the upper limit on the difference between the local mean received power from the dominant BS and that from any other member of the active group (in decibels), where the term "dominant" refers to the BS with the lowest path loss to the MS. We assume that the MS is equipped with a Rake receiver capable of performing "maximal ratio combining" of the signals it receives from the transmitting BSs. We present general analytical derivations along with results derived for specific situations through simulations and numerical integration.